PELANGGARAN TATA TERTIB SEKOLAH SISWA DI SMP NEGERI 22 PONTIANAK BESERTA BANTUANNYA - Wulan Ramadhani; Indri Astuti; Yuline Yuline (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
Abstract      Vilation is a deviant behavior to act according to one’s own will without regard the    that have been made.Code of conduct is set regulations made in writing, and bind community members. Regulatory regulations order and orderliness in school discipline include, obligations, and prohibitions. Therefore, researches want to know more about the behavior of violations of school discipline by students in SMP Negeri 22 Pontianak. The problem in this study is “how is the behavior violating school in SMP Negeri 22 Pontianak ?” This study aims to obtain an overview of the behavior of violatons of school discipline by students in SMP Negeri 22 Pontianak. The methods used is descriptive methods and the form of research is a survey study. The sample in this study were 29 class students VII in SMP Negeri 22 Pontianak. This study uses a quantitative approach. Data collection techniques used are indirect communication techniques and direct communication with data collection tools in the form of questionnaires and interviews. While the data analysis technique uses percentage calculations. Based on the results of data analysis from student behavior violations research in school SMP Negeri 22 Pontianak obtain results, namely the form of violations 56% with the category of “medium”, internal factors that affect violations of discipline 48% with the category of “medium”, external factors that affect 55% violations of the order with category “medium”, and the impact of violations of discipline 46% in the “medium” category. Keywords:Violations  Discipline Students